Smooth muscle cell-targeted RNA ligand promotes accelerated reendothelialization in a swine peripheral injury model - Beilei Lei; Linda B. Liu; Lauren Stokes; Paloma H. Giangrande; Francis J. Miller, Jr; Saami K. Yazdani (Elsevier, 2023)
The local delivery of antiproliferative agents to inhibit neointimal growth is not specific to vascular smooth muscle cells (VSMC) and delays reendothelialization and vascular healing. This investigation was intended to evaluate the effect of luminal delivery of a VSMC-specific aptamer on endothelial healing. The impact of an RNA aptamer (Apt 14) was first examined on the migration and proliferation of primary cultured porcine aortic endothelial cells (ECs) in response to in vitro scratch wound injury. We further evaluated the impact of Apt 14 on reendothelialization when delivered locally in a swine iliofemoral injury model. Although Apt 14 did not affect EC migration and proliferation, in vitro results confirmed that paclitaxel significantly inhibited EC migration and proliferation. En face scanning electron microscopy demonstrated confluent endothelium with elongated EC morphology in Apt 14-treated arteries 14 and 28 days post-treatment. In contrast, vessels treated with paclitaxel-coated balloons displayed a cobblestone morphology and significant platelet and fibrin attachment at cell junctions. These results provide the first evidence of the efficacy of a cell-targeted RNA aptamer to facilitate endothelial healing in a clinically relevant large animal model.